Skrining dan konseling gizi rutin dapat meningkatan kewaspadaan terhadap penyakit degeneratif - Sari, Indah Purnama; Ningsih, Windi Indah Fajar; Arinda, Ditia Fitri; Najmah, Najmah; Utama, Feranita (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2022)
The degenerative disease occurs because of a reduction in the body’s organs’ function. Generally, it occurs in the elderly but nowadays younger people in their productive age also could experience the disease. It can be detected through regular medical checks and the prevention of risk factors. Regular Health Check-ups requires self-awareness, but not everyone is aware to do so. Community service activities with village lecture schemes for degenerative disease dietetic courses were attended by 25 students. Community service activities aimed at increasing public awareness of degenerative diseases by screening and nutritional counseling regularly, namely 3 points of time measurements in 30 days. Measurements were conducted on body composition, blood pressure, blood sugar levels, and cholesterol levels. The results are used as reference data for eating management during counseling. There were 53 residents who voluntarily participated. The activity was carried out in Kelurahan 13 Ulu in the Bingen Culinary Village, which is a study program fostered village. The results showed an improvement where 36 people who had hypertension at the initial examination (65.5 %) has decreased to 30 people (54.5 %), high cholesterol levels at the initial examination were 20 people (36.3 %) to 9 people (16.3 %), overweight 40 people (72.7 %) to 39 people (70.0 %). It could be happened because of respondents’ awareness of their initial results supported by their understanding of the importance of eating management based on their health check results.